Exploring BeagleBone tools and techniques for building with embedded Linux - Molloy, Derek 1973- (Wiley, 2015)
This book will help you in bringing gadgets, gizmos and robots to life using the BeagleBone embedded Linux platform. You'll also learn the underlying engineering techniques that will allow you to create your own projects. Topics include: a primer on essential skills; communication, control, and advanced applications using C/C++. BeagleBone has applications in smart buildings, robot control, environmental sensing. Expansion boards and peripherals dramatically increase the possibilities. You will get up to speed on embedded Linux, electronics, and programming; master interfacing electronic circuits, buses and modules; explore the Internet-connected BeagleBone and the BeagleBone with a display; apply the BeagleBone to sensing applications, including video and sound; explore the BeagleBone's programmable real-time controllers. --
Includes bibliographical references and index. - Vendor-supplied metadata
Keywords: Linux; BeagleBone (Computer); Embedded computer systems; Operating systems (Computers); BeagleBone Black (Computer) -- Programming; BeagleBone (Ordinateur); Systèmes enfouis (Informatique); Systèmes d'exploitation (Ordinateurs); BeagleBone Black (Ordinateur); Programmation; operating systems; COMPUTERS; Computer Science; COMPUTERS; Hardware; General; COMPUTERS; Machine Theory